Velvet Worms (Onychophora) in Folklore and Art: Geographic Pattern, Types of Cultural Reference and Public Perception - Monge-Nájera, Julián (2015)
Aims: To document and preserve folkloric beliefs and art inspired by velvet worms (Onychophora), rare invertebrates that are considered "living fossils", have full placental organs and capture prey with a rough "net" built in a fraction of a second. Study Design: This study is a combination of field interviews, online surveys and automatic database search. Methods: We asked open-ended questions to farmers who know the worms, consulted experts and searched the Internet to document folkloric and artistic instances using all the names that these animals receive in English, Spanish and Portuguese (languages of the countries where they occur) as well as other languages, and automatic image search, in Web of Science, CrossRef, Google Scholar and Google. Results: We found more than 80 cases of direct references to velvet worms in folklore and art, mostly from the USA, Australia, Brazil, Costa Rica and New Zealand. Per capita the countries with more cases are New Zealand (24 cases per million inhabitants), Costa Rica (16 cases per million inhabitants) and Australia (3 cases per million inhabitants). The most frequent expressions are cartoons, followed by tourism agencies using velvet worms in their ads, products with velvet worm representations, folkloric beliefs, and music bands or songs named after them. In almost all cases the animals are seen in a favorable light, inspiring folklore and art that highlight their extraordinary nature. Conclusion: The unique prey capture mechanism of velvet worms seems to have inspired an unexpected number of artistic and folkloric expressions, preserved for the future in the present article, which starts a totally new line of research: the effect of "living fossils" on human culture.